Interactions, induced by heating, of whey protein isolate (WPI) with sugar beet pectin (SBP) in solution: Comparisons with a dry-state Maillard reaction. (October 2018) - Xiao, Yingping; Qi, Phoebe X.; Wickham, Edward D.
Abstract: We investigate changes in the molecular structures of whey proteins (WPI) caused by heat-induced interaction and reaction with varying concentrations of sugar beet pectin (SBP) in aqueous solution at neutral pH. The resulting complexes were examined using circular dichroism (CD) and steady-state and time-resolved fluorescence spectroscopic techniques. Far-UV CD spectroscopy combined with spectral deconvolution revealed noticeable reduction (up to 5%) in the amount of antiparallel β-sheet element of WPI upon interacting with SBP. Analyses from the UV-VIS and steady-state fluorescence spectroscopies showed changes in the molecular electronic states of both WPI and the feruloyl moieties of SBP upon heat-induced interaction and conjugation. The tertiary structural contacts in WPI, studied by the intrinsic Trp fluorescence, were also disrupted in the presence of SBP in the form of FRET (Fluorescence Resonance Energy Transfer) complexes, most noticeably at a high level of SBP (3%), contrasting to the results from dry-heating. The thermal stability of WPI, at both secondary and tertiary structural levels, did not increase considerably by interacting and conjugating with SBP, especially at an equal concentration of SBP (3%). However, the stability of feruloyl groups of SBP saw moderate improvement and was less pronounced than that of the dry-state reactions. Graphical abstract: Image 1 Highlights: Reduced level of molecular interactions between WPI and SBP when heated in solution. Over 5% loss in antiparallel β-sheet in WPI at an equal concentration of SBP (3%). FRET complexes formed in solution are less stable than those in the dry-state. Trp environment of WPI sees reduced protection by SBP compared to the dry-state. Moderate increase in thermal stability of WPI by reacting and interacting with SBP.